Application of Finite Element Method to American Option with Dividen - F. WYRASTI (NIM 20105003), ANDI
Option is a financial instrument that gives rights to the owner to buy or sell an asset at the price with a defined time and price. One type of option is an America option which able to exercised any time before expired untill expiration date. Determining the optimal time to exercised an American option is more difficult, because the solution cannot be found directly. Specially if the American option pays dividend so that the price of the underlying asset will be falling down after dividend payment. In this thesis, will be used the Jamshidian's partial differential equations (PDE), as a modification of Black-Scholes PDE, for the American call options and for the American put options where H is an indicator function. This PDE is solved numerically with the finite element methods (FEM). Then the result wil be compared with some previous work.